(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Panchkarma is a therapeutic process of Ayurveda wherein the vitiated Doshas are expelled out of the patient’s body, leading to detoxification of the body. It is also useful in diseases of children like cerebral palsy, muscular dystrophy, autism, attention deficit hyperactivity disorder, rhinitis, etc. Materials: Available research literature in PubMed, Scopus, Google Scholar, DHARA and Ayush Research Portal was searched extensively for the Panchkarma in children. Journals published online in last 20 years were considered. Ayurveda classical texts were also referred. Observations: Panchkarma therapies like Abhyanga, Shashti shali pinda sweda and Basti have significant results in Spastic Cerebral Palsy. Bell`s palsy can be treated with Shiro-abhyang, Nasya and Pata sveda. Disorders like DMD, AS, ADHD and constipation are shown to be managed well with Panchkarma procedures. Conclusion: Panchkarma procedures are very effective in diseases of children like cerebral palsy, Bells’s palsy, muscular dystrophy, autism, attention deficit hyperactivity disorder and constipation. Thus, it needs to be widely publicized for use in children along with oral medications for maximum benefits.